Personal Spiritual Experience as The Foundation of Authentic Islamic Counseling: Phenomenological Findings on the Concept of Heart Communication Therapy - Mayasari, Ros; Zaujah, Ainun; Bintang, Sri An Maharani (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
This study aims to explore the reflective experiences of a family counselor in formulating Qalbu Communication Therapy (TKQ) as an Islamic counseling approach based on personal and spiritual experiences. The study uses a qualitative method with a phenomenological approach. Data were collected through participants’ reflective notes and interviews, then analyzed using thematic analysis techniques. The results of the study show three main findings. First, the counselor’s personal and spiritual crisis experiences served as an important energy source in formulating counseling innovations. Second, the application of TKQ not only helped clients find peace, but also encouraged social transformation through the formation of spirituality-based counseling communities. Third, the counseling process gave rise to empowerment, whereby some clients developed into community counselors. The conclusion of this study confirms that counselors’ life experiences and spiritual reflections can be an authentic source in the development of Islamic counseling. Counseling does not stop at individual recovery but develops into a participatory, creative, and sustainable model of social empowerment.